Maryland's Global Budget Revenue Model: How Do Costs and Readmission Rates Fare for Patients Undergoing Total Knee Arthroplasty? - Delanois, Ronald E.; Wilkie, Wayne A.; Mohamed, Nequesha S.; Remily, Ethan A.; Pollak, Andrew N.; Mont, Michael A. (The Journal of Knee Surgery, 2020)
In 2014, Maryland implemented the Global Budget Revenue (GBR) model for cost reduction and quality improvement. This study evaluated GBR's effect on demographics and outcomes for patients who underwent primary total knee arthroplasty (TKA) by comparing Maryland to the United States (U.S.). We identified primary TKA patients in Maryland's State Inpatient Database (n = 71,022) and the National Inpatient Sample (n = 4,045,245) between 2011 and 2016 utilizing International Classification of Disease (ICD)-9 and ICD-10 diagnosis codes. Multiple regression was used for difference-in-difference (DID) analyses to compare the intervention cohort (Maryland) to the nonintervention cohort (U.S.) between the pre-GBR (2011–2013) and post-GBR (2014–2016) periods. After GBR implementation, there were proportionally less white, obese, morbidly obese, Medicare, and Medicaid patients with proportionally more routine discharge patients in Maryland and the U.S. (all p < 0.001). There were proportionally less home health care (HHC) patients in Maryland, but more in the U.S. (both p < 0.001). The mean lengths of stay (LOS), costs, and complications decreased for both cohorts, while charges increased for the U.S. (all p < 0.001). The DID analysis suggested Maryland saw more Asian and Medicaid patients and less obese and morbidly obese patients under GBR. The DID assessments also found decreased LOS, costs, and charges (p < 0.001 for all) for patients under GBR. As other states such as Pennsylvania and Vermont explore hospital budgets, Maryland may provide a more viable model for future health care policies that incorporate global budgets.
Keywords: total knee arthroplasty; global budget revenue; health care economics